Application of Risk Management in Development Noor Halal Minimarket at Islamic Education Institutions - Meydi Nindia Larasati; Rhian Indradewa; Tantri Yanuar Rahmat Syah; Diana Fajarwati (Journal of Multidisciplinary Academic, 2020)
The development of minimarkets in Indonesia is currently growing. The national minimarket network owned by large companies makes conventional stores and local minimarkets has been decreased in competitiveness. Here, the national minimarket provides a variety of facilities offered to make customers comfortable to shop. The competition with the national minimarket network is a challenge faced in the local minimarket business. Thus, a minimarket has innovation and strategy to brings actual solutions along with the times also changes to win the competition. Here, the Noor Halal Minimarket in this case chose Islamic Education Institution as an untapped market niche, especially in Bogor Regency, West Java due to have the large number of Islamic center education. Another strategy that is a mainstay is to use innovation vending machine in daily operations for the efficiency and application of tiered prices following a certain number of purchases.